2013
DOI: 10.3109/0886022x.2013.836750
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between iron stores and QTc dispersion in chronic ambulatory peritoneal dialysis patients

Abstract: Although prolonged QTc, QT dispersion and QTc dispersion were suggested as the markers of ventricular arrhythmias we did not find any significant difference in regards to these parameters between control patients and CAPD patients. But the high body iron stores in these patients increase the risk of increased QT dispersion. The concern over iron overload in dialysis patients is not only because of its oxidative toxicity, but also its precipitation of arrhythmias, which may be measured by the surrogate marker o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…Additionally, elevated serum ferritin levels have been observed in patients with renal impairment, and these elevated levels are closely related to a higher risk of CKD, a rapid decline in renal function and progression to renal replacement therapy (RRT) [22][23][24]. Accumulating evidence has demonstrated that hyperferritinemia is significantly associated with poor prognosis, including higher mortality in MHD and PD patients [6,[25][26][27], although the threshold values at which serum ferritin contributes to negative outcomes differ between MHD and PD patients; these ferritin levels are higher than the demand for erythropoiesis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, elevated serum ferritin levels have been observed in patients with renal impairment, and these elevated levels are closely related to a higher risk of CKD, a rapid decline in renal function and progression to renal replacement therapy (RRT) [22][23][24]. Accumulating evidence has demonstrated that hyperferritinemia is significantly associated with poor prognosis, including higher mortality in MHD and PD patients [6,[25][26][27], although the threshold values at which serum ferritin contributes to negative outcomes differ between MHD and PD patients; these ferritin levels are higher than the demand for erythropoiesis.…”
Section: Discussionmentioning
confidence: 99%
“…[16] It was also observed in study of Bavbek et al, who examined peritoneal dialysis patients, that increased iron stores were associated with prolonged QTd. [17] Patients with prolonged QTd have higher levels of iron and transferrin saturation. Numerous studies have revealed the fact that iron overload plays a role in the pathogenesis of atherosclerosis and is associated with deaths related to coronary artery diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Jos perteklius HD pacientams sukelia oksidacinį stresą ir gali pagreitinti aritmijų atsiradimą. Didelės geležies atsargos PD pacientams yra susijusios su didesne QT dispersija [38].…”
Section: Elektrokardiografiniai Pokyčiaiunclassified